The Effect of Village Fund Management Accountability and Village Policy on Community Welfare - Ujang Wahyu Utomo; Sudrajat; Fajar Gustiawaty Dewi (HM Publisher, 2022)
The village fund program aims to provide services to rural communities, maximum economic recovery, the main program of the central government according to village authority, adjustment of new village habits, and the main thing is the achievement of village community welfare. This study aims to determine the effect of village fund management accountability and village policies on community welfare. The study took place in the Tulang Bawang area by determining as many as 19 villages spread over 5 sub-districts out of 147 villages in 15 sub-districts in the Tulang Bawang district. The research variable consisted of the independent variable, namely the accountability of village fund management (X1) and village policies (X2), and the dependent variable in the form of community welfare (Y). The influence of the accountability variable for village fund management on community welfare produces a path coefficient value of 0.237 with a T-statistic of 1.349 and P values of 0.178. The influence of village policy variables on community welfare produces a path coefficient value of 0.299 with a T-statistic of 1.835 and P values of 0.067. In conclusion, accountability for the financial management of village funds does not affect the welfare of the community. Meanwhile, village policies have a positive effect on the welfare of the community in Tulang Bawang village.